Composting and compost application: Trade-off between greenhouse gas emission and soil carbon sequestration in whole rice cropping system. (1st March 2019) - Jeong, Seung Tak; Cho, Song Rae; Lee, Jeong Gu; Kim, Pil Joo; Kim, Gil Won
Abstract: Manure application showed contrasting effects on soil quality and greenhouse gas (GHG) emissions, in particular methane (CH4 ) emissions in a rice cropping system. Therefore, to mitigate CH4 emissions, stabilized manure like compost is recommended without considering the additional GHG emissions during the industrial processes and soil organic carbon (SOC) stock changes. To determine the integrated effect of compost utilization on the net global warming potential (GWP) of a rice cropping system, the fluxes of GHGs during the whole process were computed using a life cycle assessment (LCA) method. The model framework was composed of GHG fluxes from two compartments: the industrial activities, and the composting and rice cropping processes. Since manure application can increase SOC stock, the annual SOC stock changes were analyzed by the net ecosystem C budget (NECB). Manure applications significantly increased rice productivity and the net primary production (NPP) as a C input source without difference between fresh and composted manures. NPK+fresh manure application significantly increased CH4 and N2 O emissions by 81% and 37% over the NPK treatment in rice cropping system, respectively, and depleted SOC stock with 1.3 Mg C ha −1 year −1, due to priming effect. As a result, NPK+fresh manure application increased the net GWP by 80% over the NPK treatment. In comparison, NPK+compost utilization decreased the net GWP by 30% over that of the NPK+fresh manure during the whole process. Manure composting increased the GWP of the industrial processes by 7%, but the 20% reduction of CH4 flux and 0.5 Mg C ha −1 year −1 of SOC stock increase significantly decreased the net GWP during the whole rice cropping process. As a result, the GHG intensity which means the net GWP per gain yield was not different between the NPK+composted manure and the NPK treatments. In conclusion compost application can be a reasonable soil management strategy to reduce GHG emission impact and to increase crop productivity in rice cropping systems. Graphical abstract: Highlights: Compost application was effective to increase rice productivity and soil carbon stock. Compost application significantly decreased CH4 emission over the fresh manure in rice field. Greenhouse gas emission during composting negligibly contributed to increase the net GWP in the whole rice cropping system. Compost utilization decreased the net GWP by 30% over the fresh manure in the whole rice cropping process.